Testing the new Keynesian Phillips curve - Gunnar Bårdsen; Eilev S. Jansen; Ragnar Nymoen (University of Oslo, Department of Economics, 2002)
The dynamic properties of the The New Keynesian Phillips curve (NPC) is analysed within the framework of a small system of linear di.erence equations.We evaluate the empirical results of existing studies which uses `Euroland' and US data. The debate has been centered around the goodness-of-fit, but this is a weak criterion since the NPC-fit is typically well approximated by purely statistical models (e.g., a random walk). Several other parametric tests are then considered, and the importance of modelling a system that includes the forcing variables as well as the rate of inflation is emphasized. We also highlight the role of existing studies in providing new information relative to that which underlies the typical NPC. This encompassing approach is applied to open economy versions of the NPC for UK and Norway.
Keywords: C22; C32; C52; E31; E52; 330; New Keynesian Phillips curves; US inflation; Euro inflation; UK inflation; Norwegian inflation; Monetary policy; Dynamic stability conditions; Evaluation; Encompassing tests; Phillips-Kurve; Ungleichgewichtstheorie; Inflation; Geldpolitik; Wirtschaftspolitisches Ziel; Schätzung; USA; Norwegen; EU-Staaten; Großbritannien